Fish Meal Replacement by Chicken By-Product Meal in Diet: Impacts on Growth and Feed Availability of Juvenile Rockfish (Sebastes schlegeli), and Economical Analysis - Ran Li; Sung Hwoan Cho (Animals)
A 56-day feeding experiment was carried out to evaluate the effects of substituting fish meal (FM) with chicken by-product meal (CBM) in diets on the growth and feed utilization of rockfish (Sebastes schlegeli). Six experimental diets were formulated to be isonitrogenous and isolipidic. The control (Con) diet included 55% FM. In the Con diet, 10%, 20%, 30%, 40%, and 50% of FM was replaced with CBM, named as the CBM10, CBM20, CBM30, CBM40, and CBM50 diets, respectively. A total of 540 juvenile fish were distributed into 18 tanks (30 fish per tank and 3 tanks per diet) and fed to apparent satiation two times daily for 56 days. The weight gain and specific growth rate of rockfish fed the CBM10 and CBM20 diets were comparable to rockfish fed the Con diet. The feed consumption of rockfish fed the Con and CBM10 diets was significantly (p < 0.001) higher than that of fish fed all other diets, except for the CBM20 diet. However, protein retention, biometric indices, chemical composition, amino acid profiles, and plasma and serum parameters of rockfish were not significantly influenced by dietary FM substitution with CBM. The Con, CBM10, and CBM20 diets showed superior (p < 0.001) economic profit index (EPI) compared to the CBM30, CBM40, and CBM50 diets. Conclusively, FM up to 20% could be substituted by CBM in diets without impairing growth, feed availability, chemical composition, amino acid profiles, and blood parameters of rockfish grown from 2.5 g to 12.5 g. However, the long-term effects of CBM substitution or the potential use of combined CBM and other alternative protein sources for FM in rockfish diets are needed in future.